Financial Statement Quality in the Public Sector: Internal Control over Reporting as a Moderating Factor - Chintya Maharani Putri; Iwan Triyuwono; Virginia Nur Rahmanti (Jurnal Reviu Akuntansi dan Keuangan, 2025)
Purpose: This study aims to test and explain the determinants of the quality of financial statement information in government mechanisms by highlighting the moderating role of internal control over financial reporting (ICoFR). Methodology/approach: A quantitative approach is used through the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. Findings: The results showed that the competence of the Human Resources and Internal Audit function improved the quality of financial statement information. In contrast, implementing of the Institutional Level Financial Application System and following up on audit findings do not directly impact the quality of financial statement information. While Internal Control over Financial Reporting strengthens the role of internal audit and the effectiveness of follow-up on audit findings, but if applied too strictly, it weakens the positive impact of the Institutional Level Financial Application System, resulting in less-than-optimal benefits for financial statement quality. Practical implications: These results emphasize the importance of integrating control systems, HR competencies, and technology systems to achieve public sector financial governance reform effectively. Originality/value: This study offers novelty by presenting ICOFR as a structural moderator that strengthens the synergy between variables in the Stewardship Theory framework.